2010
DOI: 10.2298/abs1003565k
|View full text |Cite
|
Sign up to set email alerts
|

Inversion polymorphism in populations of Drosophila subobscura from urban and non-urban environments

Abstract: Populations of Drosophila subobscura from the urban area of Belgrade and from the locality, Deliblato, which is not under strong anthropogenic influence, were studied with the aim to characterize and compare their genetic structure by examining chromosomal inversion polymorphism. Additional analysis and comparison of this type of polymorphism with several other populations from different habitats in the central Balkans, was done. The obtained results indicate higher heterozygosity in the population from Belgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…In G 0 , the inversions (or chromosomal arrangements) and karyotypes found are characteristic of the Avala mountain population (Zivanovic and Mestres 2010a) and also of the Balkan region (Zivanovic et al 1995(Zivanovic et al , 2002Zivanovic 2007;Rasic et al 2008;Stamenkovic-Radak et al 2008;Kenig et al 2010;Zivanovic and Mestres 2011;Jelić et al 2012). No significant changes between G 0 and G 12 were observed for the inversion and arrangement frequencies.…”
Section: Discussionmentioning
confidence: 94%
“…In G 0 , the inversions (or chromosomal arrangements) and karyotypes found are characteristic of the Avala mountain population (Zivanovic and Mestres 2010a) and also of the Balkan region (Zivanovic et al 1995(Zivanovic et al , 2002Zivanovic 2007;Rasic et al 2008;Stamenkovic-Radak et al 2008;Kenig et al 2010;Zivanovic and Mestres 2011;Jelić et al 2012). No significant changes between G 0 and G 12 were observed for the inversion and arrangement frequencies.…”
Section: Discussionmentioning
confidence: 94%
“…Urban and non‐urban populations of Drosophila subobscura from Serbia had their genetic structure examined, using chromosome inversions as markers. Despite a strong anthropogenic influence on the population from Belgrade, it did not show any loss in its inversion polymorphisms, as well as in its population size; therefore, this population does not seem to suffer the negative effects caused by human activity and urbanization (Kenig, Jelic, Kurbalija, Stamenkovic‐Radak, & Andjelkovic, ). Their results suggest that divergence in chromosome inversion polymorphisms among Serbian populations of D. subobscura may be an adaptive response to differences among environments they live in (Stamenković‐Radak et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…ns, non-significant; *p < 0.05; **p < 0.01; ***p < 0.001 CV: Capivari; SG: Santa Genebra; CS07: Costa e Silva; CA: Colinas do Atibaia; IT: Itatiaia; TE: Teresópolis. population size; therefore, this population does not seem to suffer the negative effects caused by human activity and urbanization (Kenig, Jelic, Kurbalija, Stamenkovic-Radak, & Andjelkovic, 2010).…”
Section: Markermentioning
confidence: 99%
“…Initial inter-population differences in chromosome arrangement frequencies were expected if we take into account the previous analysis of chromosomal polymorphism of the populations from the same locations [ 23 ]. The differences are due to the diverse evolutionary history of each population originating from ecologically distinct habitats.…”
Section: Discussionmentioning
confidence: 99%
“…subobscura showed that a higher resistance was present in a population originating from the more polluted locality [ 21 ]. It was also found that the extent of inversion polymorphism was higher in urban Drosophila populations, which was a result of the large number of ecological niches in this type of environment [ 22 , 23 ]. However, only few studies have analyzed how historical differences in inversion polymorphisms affect the ability of populations to respond to new environmental conditions, although the prediction of population-specific genetic response to heavy metal pollution is one of the most important tasks of ecotoxicology [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%